THE EFFECT OF KAHOOT PLATFORM USE ON COMPUTER SCIENCES STUDENTS’MOTIVATIONIVATION - BENABBOU, HAKIMA (My University, 2020)
The recent educational technologies such as mobile platforms have facilitated the ongoing process of teaching and learning. The aim of the present work is to check the effectiveness of using Kahoot platform on computer sciences students’ motivation. This study attempted to investigate whether the use of Kahoot affects positively on ESP students’ engagement and their learning outcomes. Hence, to achieve the mentioned objectives, the study was a quantitative and qualitative research; students’ questionnaire was administrated to master one computer sciences student and an interview was conducted toESP teachers at the department of Exact Sciences in Chlef University. The main findings of this research unveil the teachers’ satisfaction of the effect of Kahoot on students’ motivation and their learning outcomes. Finally, the study suggested some recommendation to ESP teachers in order to ameliorate the learning outcomes and facilitate the teaching process.
Case of First year Master Computer Sciences Students at Chlef University
Case of First year Master Computer Sciences Students at Chlef University
Keywords: Mobile platforms; Motivation; Learning outcomes; Kahoot; ESP